SISTEM MONITORING ENERGI LISTRIK PADA KOMPOR PENGHASIL LISTRIK DENGAN TEKNOLOGI INTERNET OF THINGS (KOLISS-IOT - Muhammad Reza Faleva; Dian Budhi Santoso; Lela Nurpulaela (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2020)
Electricity has become a basic need of society today. Alternative energy sources are one of the ways to help people in providing electrical energy, therefore an internet of things-based electric stove technology (KOLISS-IoT) is needed. technology. A monitoring tool is needed so that it is known how much the performance of the KOLISS-IoT technology in producing electrical energy. The tool designed to monitor this requires a voltage and current sensor, and Arduino. Current sensor uses INA219 sensor which functions to detect how much voltage and power current is generated by KOLISS-IoT. Arduino and ESP8266 modules are needed to process data and send data using IoT technology. The results can be displayed on a 16x2 I2C lcd and webpage using the ESP8266 module. The test results obtained through measurements using the sensor voltage, current, and power by the INA219 sensor are at an average of 2.65V for the calculation of the voltage, 0.031A for the calculation of the current and 0.0785W for the calculation of power. The maximum values ??of voltage, current and power in the test are 2.85 V, 0.068A, and 0.194W.